Pharmacological and structural insights into nanvuranlat, a selective LAT1 (SLC7A5) inhibitor, and its N-acetyl metabolite with implications for cancer therapy - Chunhuan Jin; Xinyu Zhou; Minhui Xu; Hiroki Okanishi; Ryuichi Ohgaki; Yoshikatsu Kanai (Scientific Reports)
Abstract L-type amino acid transporter 1 (LAT1, SLC7A5), overexpressed in various cancers, mediates the uptake of essential amino acids crucial for tumor growth. It has emerged as a promising target for cancer therapy. Nanvuranlat (JPH203/KYT-0353), a LAT1 inhibitor, has shown antitumor activity in preclinical studies and efficacy in biliary tract cancer during clinical trials. This study provides a comprehensive pharmacological characterization of nanvuranlat and its N-acetyl metabolite, including structural insights into their LAT1 interactions. Both compounds demonstrated high selectivity for LAT1 over LAT2 and other amino acid transporters. Nanvuranlat acts as a competitive, non-transportable LAT1 inhibitor (K i = 38.7 nM), while its N-acetyl metabolite retains selectivity but with reduced affinity (K i = 1.68 µM). Nanvuranlat exhibited a sustained inhibitory effect on LAT1 even after its removal, indicating the potential for prolonged therapeutic effects. Both compounds showed comparable dissociation rates, suggesting that N-acetylation does not affect the interaction responsible for slow dissociation. The U-shaped conformation adopted by nanvuranlat when bound to LAT1 likely contributes to its high affinity, selectivity, sustained inhibitory effect, and non-transportable nature observed in this study. These insights into nanvuranlat’s mechanism and metabolic impact provide essential information for understanding its clinical efficacy and advancing LAT1-targeted cancer therapies.